Strategy for Accurate Detection of Escherichia Coli O157:H7 in Ground Pork Using a Lateral Flow Immunoassay - Song Cheng; Ming-hui Chen; Gang-gang Zhang; Zhi-biao Yu; Dao-feng Liu; Yong-hua Xiong; Hua Wei; Wei-hua Lai (Sensors, 2017)
Escherichia coli O157:H7 is known to cause serious diseases including hemorrhagic colitis and hemolytic uremic syndrome. A gold nanoparticle lateral flow immunoassay (Au-LFIA) was used to detect Escherichia coli O157:H7 in ground pork samples. False-positive results were detected using Au-LFIA; a Citrobacter freundii strain was isolated from the ground pork samples and identified by using CHROmagarTM plates, API 20E, and 16S RNA sequencing. Since C. freundii showed cross-reactivity with E. coli O157:H7 when Au-LFIA test strips were used, a novel method combining modified enrichment with a lateral flow immunoassay for accurate and convenient detection of E. coli O157:H7 in ground pork was developed in this study to minimize these false positives. MacConkey broth was optimized for E. coli O157:H7 enrichment and C. freundii inhibition by the addition of 5 mg/L potassium tellurite and 0.10 mg/L cefixime. Using the proposed modified enrichment procedure, the false-positive rate of ground pork samples spiked with 100 CFU/g C. freundii decreased to 5%.